1990
DOI: 10.1680/geot.1990.40.3.329
|View full text |Cite
|
Sign up to set email alerts
|

On the compressibility and shear strength of natural clays

Abstract: The compressibility and strength characteristics of reconstituted clays are used as a basic frame of reference for interpreting the corresponding characteristics of natural sedimentary clays. The properties of reconstituted clays are termed ‘intrinsic’ properties since they are inherent to the soil and independent of the natural state. The properties of a natural clay differ from its intrinsic properties due to the influence of soil structure (fabric and bonding). Thus the intrinsic properties provide a frame … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

61
989
2
100

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,457 publications
(1,152 citation statements)
references
References 20 publications
61
989
2
100
Order By: Relevance
“…In his fortieth Rankine lecture, Burland (1990) by an italic and subscript v. Hence, e v indicates the void ratio associated with the vertical 140 effective stress. For two parameters introduced in this study, differences exist between the 141 parameters used in the two systems: the parameters * 100 e (the void ratio of the soil in a 142 reconstituted state at p = 100 kPa) and * 1000 e (the void ratio at p = 1,000 kPa …”
Section: Burland's Work On the Compression Behaviour Of Reconstitutedmentioning
confidence: 99%
See 1 more Smart Citation
“…In his fortieth Rankine lecture, Burland (1990) by an italic and subscript v. Hence, e v indicates the void ratio associated with the vertical 140 effective stress. For two parameters introduced in this study, differences exist between the 141 parameters used in the two systems: the parameters * 100 e (the void ratio of the soil in a 142 reconstituted state at p = 100 kPa) and * 1000 e (the void ratio at p = 1,000 kPa …”
Section: Burland's Work On the Compression Behaviour Of Reconstitutedmentioning
confidence: 99%
“…properties (e.g., Skempton, 1944;Bowles, 1989;Muir Wood, 1990; Burland, 1990;Sridharan 443 and Nagaraji, 2000; Horpibulsuk et al, 2013). Based on these studies, the virgin compression 444 index of a clay can usually be estimated from the liquid limit or the initial void ratio of the 445 soil.…”
mentioning
confidence: 99%
“…Burland [6] stated that much modern soil mechanics has developed from the results of careful, comprehensive studies of the properties of remolded or reconstituted natural soils or artificial materials such as kaolinite or illite. Kaolin used in the present work, is made of clayey minerals dominated by the kaolinite, derived essentially from the alteration of Felds path alkaline and micas with a density of 2.62.…”
Section: Methodsmentioning
confidence: 99%
“…Kaolin used in the present work, is made of clayey minerals dominated by the kaolinite, derived essentially from the alteration of Felds path alkaline and micas with a density of 2.62. Previous research has shown that the kaolin structure possesses great advantages in many processes due to its high chemical stability and low expansion coefficient [7,8]. The importance of kaolin is remarkable as one of the most abundant mineral in soils and sediments, its properties are such that it interacts with other soil elements and contribute to the mechanical stability of the soils [9,10].…”
Section: Methodsmentioning
confidence: 99%
“…The permeability values (K) for the Rupel Clay Member underneath the Westerschelde were extrapolated to greater depths and yielded values ranging Netherlands Journal of Geosciences / Geologie en Mijnbouw 82 (1) Vertical pressure [MPa] Void ratio (e) (Burland, 1990); SCL = Sedimentary Compression Line, which approaches compression of clay under natural geological conditions; solid arrow = pre-consolidation stress, open arrow = effective in-situ stress including a load of a 1000-metre-thick ice cover. from 1.2 x 10 -11 m/s to 5.4 x 10 -15 m/s.…”
Section: Oedometer Testsmentioning
confidence: 99%